Library Management in a Changing Environment: 25th IATUL Conference, May 30 - June, 2004 - Patricia B. Yocum (Issues in Science and Technology Librarianship, 2004)
The article summarizes the 25th IATUL Conference, which took place in Krakow, Poland from May 30 - June 3, 2004.